DevOps: Concept, Technology and Tools - Deshwal, Pallavi; Ghuli, Poonam (International Journal of Computer Sciences and Engineering, 2020)
DevOps is a new concept that consolidates development and operations team to intently incorporate individuals, procedures and innovation for automated end to end delivery and deployment of software. DevOps Engineers have start to finish obligation of the Application (Software) directly from gathering the prerequisite to improvement, to development, to testing, to application deployment lastly checking and assembling input from the end clients, again implement the changes as per end client requirements. This paper presents DevOps concept, how it has been evolved from traditional methods, technologies involved such as CI/CD pipeline, project gating and DevOps tools that automates the software development cycle